Education level is associated with neuropsychiatric symptoms in patients with amnestic‐mild cognitive impairment. Issue 3 (18th February 2022) - Inamura, Keisuke; Shinagawa, Shunichiro; Nagata, Tomoyuki; Tagai, Kenji; Nukariya, Kazutaka; Shigeta, Masahiro
Abstract: Background: We examined differences in the severity of neuropsychiatric symptom (NPS) subsyndromes according to education level among patients with amnestic‐mild cognitive impairment (a‐MCI) with the aim of identifying patient demographics related to NPS subsyndromes. Methods: Overall, 140 patients with a‐MCI were included. We divided the patients into three groups according to their educational level (primary education, middle education, and high education) and compared their demographics. To explore the severity of NPS subsyndromes according to educational level, we used the Neuropsychiatric Inventory (NPI) after adjustments for the Mini‐Mental State Examination (MMSE) score. Finally, NPS subsyndromes that were identified as being related to educational level were further explored using a general linear model (GLM). Results: Significant differences in several demographics were observed among the three groups. Among the NPS subsyndromes, the scores for aggressiveness were significantly higher in the primary and high education groups than in the middle education group, while the apathy/eating problem scores were significantly higher in the primary education group than in the other groups. The GLM analyses showed that aggressiveness was related to marital status and the Zarit Caregiver Burden Interview (ZBI‐J) score, while apathy/eating problems were related to the instrumental activities of daily living (IADL) percentage, the ZBI‐J score, and the education level in years. Conclusions: Among NPS subsyndromes, aggressiveness and apathy/eating problems differed according to education level in patients with a‐MCI. A GLM analysis suggested that not only education level, but also various other factors should be considered when determining the need for NPS interventions.